Comparison of two behavioural pain scales for the assessment of procedural pain: A systematic review - Hanne Cathrine Birkedal; Marie Hamilton Larsen; Simen A. Steindal; Marianne Trygg Solberg (Wiley, 2021)
Abstract Aim To examine the clinical utility and measurement properties of the Critical‐Care Pain Observation Tool and the Behavioural Pain Scale when used to assess pain during procedures in the intensive care unit. Design A systematic review was conducted, guided by the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses checklist. Methods A systematic search was conducted in CINAHL, MEDLINE, EMBASE and PsychINFO (01 October 2019). Study selection, data extraction and assessment of methodological quality were performed by a pair of authors working independently. Different psychometric properties were addressed: inter‐rater reliability, internal consistency, test-retest reliability, discriminant validity and criterion validity. Results Eleven studies were included. Both Critical‐Care Pain Observation Tool and the Behavioural Pain Scale showed good reliability and validity and were good options for assessing pain during painful procedures with intensive care unit patients unable to self‐report on pain. The Critical‐Care Pain Observation Tool is to be preferred since this tool was shown to have particularly good reliability and validity in assessing pain during procedures, but the Behavioural Pain Scale is an appropriate alternative.